Paradox of age: older patients receive higher age-adjusted minimum alveolar concentration fractions of volatile anaesthetics yet display higher bispectral index values. (September 2019) - Ni, Katherine; Cooter, Mary; Gupta, Dhanesh K.; Thomas, Jake; Hopkins, Thomas J.; Miller, Timothy E.; James, Michael L.; Kertai, Miklos D.; Berger, Miles
Abstract: Background: Minimum alveolar concentration (MAC) and MAC-awake decrease with age. We hypothesised that, in clinical practice, (i) end-tidal MAC fraction in older patients would decline by less than the predicted age-dependent MAC decrease (i.e. older patients would receive relatively excessive anaesthetic concentrations), and (ii) bispectral index (BIS) values would therefore be lower in older patients. Methods: We examined the relationship between end-tidal MAC fraction, BIS values, and age in 4699 patients > 30 yr in age at a single centre using unadjusted local regression (locally estimated scatterplot smoothing), Spearman's correlation, stratification, and robust univariable and multivariable linear regression. Results: The end-tidal MAC fraction in older patients declined by 3.01% per decade (95% confidence interval [CI]: 2.56–3.45; P <0.001), less than the 6.47% MAC decrease per decade that we found in a meta-regression analysis of published studies of age-dependent changes in MAC ( P <0.001), and less than the age-dependent decrease in MAC-awake. The BIS values correlated positively with age (ρ=0.15; 95% CI: 0.12–0.17; P <0.001), and inversely with the age-adjusted end-tidal MAC (aaMAC) fraction (ρ= –0.13; 95% CI: –0.16, –0.11; P <0.001). Conclusions: The age-dependent decline in end-tidal MAC fraction delivered in clinical practice at our institution was less than the age-dependent percentage decrease in MAC and MAC-awake determined from published studies. Despite receiving higher aaMAC fractions, older patients paradoxically showed higher BIS values. This most likely suggests that the BIS algorithm is inaccurate in older adults.